MiR-135a-3p inhibits the progression of prostate cancer by targeting TLR4 - LianQiang Li; Xiao Zhang (Cancer Biology & Therapy)
To explore the expression of miR-135a-3p in prostate cancer，analyze its effects on tumor development and the involved mechanisms. A total of 125 specimens of cancer tissues and corresponding adjacent normal tissues from prostate cancer patients were collected. Real – Time quantitative PCR was employed to quantify the expression levels of miR-135a-3p in prostate cancer tissues and cell lines. Kaplan-Meier survival curve analysis and Cox regression were performed to evaluate the prognostic significance of miR-135a-3p in prostate cancer. The CCK-8 assay was used to detect cell proliferation. A dual-luciferase reporter assay was employed to validate the targeting interaction between miR-135a-3p and Toll-like receptor 4 (TLR4). miR-135a-3p is lowly expressed in prostate cancer tissues and cells, and its low expression is associated with poor prognosis of patients. The low expression state of miR-135a-3p showed a significant correlation with TNM stage, clinical stage, Gleason score, and lymph node metastasis. In addition, miR-135a-3p inhibits the proliferation of prostate cancer cells and cancer progression by negatively regulating the expression of TLR4. miR-135a-3p is downregulated in prostate cancer and is associated with poor prognosis of patients. It exerts an inhibitory effect on the progression of prostate cancer by targeting TLR4.